2017
DOI: 10.4102/ac.v17i1.426
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing small, medium and micro-sized enterprises’ borrowing from banks: The case of the Botswana manufacturing sector

Abstract: The objective of the study: The main objective of this study is to determine the factors that influence manufacturing small, medium and micro-sized enterprises’ (SMMEs) borrowing from banks.Problem statement: This article examines factors that affect SMMEs’ ability to borrow money from commercial banks. Empirical evidence was collected from manufacturing SMMEs.Motivation for the study: There is a scarcity of studies on factors influencing borrowing among Botswana manufacturing SMMEs.Methodology: The study empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 21 publications
1
15
0
2
Order By: Relevance
“…Without awareness and knowledge acting together with financial incentives, it's difficult to link CSA practices to outcomes, do a cost-benefit analysis on adoption of sustainable practices such as CSA because knowledge coupled with capacity support precedes adoption. Integration and CSA adoption require consultations with all relevant stakeholders to advise suitable interventions, incentives, and policy options [26,27,28]. Most actors may not have funds to invest and attend CSA training bearing in mind they are poor rural farmers and most actors are micro-enterprises with businesses that are mostly led by the youth and less than 5 years old, most may not have broken even and have no excess cash flow to invest in training and awareness, hence the need for free training and other incentive-driven integration approaches Investing in modern technologies such as CSA TIMPs requires financial resources, which most actors lack or have no access to, and even though they had access they would need to see the return on investment (ROI) almost immediately and bearing in mind that CSA impacts and benefits are realized in the long term compared to short term, this would discourage investment based on ROI, hence requiring some form of incentives to encourage early adopters of CSA TIMPs.…”
Section: Lack Of Property Rightsmentioning
confidence: 99%
“…Without awareness and knowledge acting together with financial incentives, it's difficult to link CSA practices to outcomes, do a cost-benefit analysis on adoption of sustainable practices such as CSA because knowledge coupled with capacity support precedes adoption. Integration and CSA adoption require consultations with all relevant stakeholders to advise suitable interventions, incentives, and policy options [26,27,28]. Most actors may not have funds to invest and attend CSA training bearing in mind they are poor rural farmers and most actors are micro-enterprises with businesses that are mostly led by the youth and less than 5 years old, most may not have broken even and have no excess cash flow to invest in training and awareness, hence the need for free training and other incentive-driven integration approaches Investing in modern technologies such as CSA TIMPs requires financial resources, which most actors lack or have no access to, and even though they had access they would need to see the return on investment (ROI) almost immediately and bearing in mind that CSA impacts and benefits are realized in the long term compared to short term, this would discourage investment based on ROI, hence requiring some form of incentives to encourage early adopters of CSA TIMPs.…”
Section: Lack Of Property Rightsmentioning
confidence: 99%
“…Pendapat lain menyatakan bahwa pelaku usaha skla mikro adalah unit usaha yang rata-rata dicirikan dengan model DAN produksi yang sederhana tanpa mensyaratkan keterampilan yang terlampau tinggi. Kesederhanaan produksi tercermin dari sifat manajemen yang tradisional dan cara bersikap (orientasi bisnis) dari para pelakunya yang bertendensi konservatif (Mutoko& Kapunda, 2017). Sifatsifat tersebut berkorelasi dengan skala usaha yang bersifat mikro, yang berbeda dengan skala usaha kecil dan menengah.…”
Section: Latar Belakangunclassified
“…The study findings are in line with those of Wambua & Munyithya, (2015) where marital status was found to be a key determinant of entrepreneurial success. Mutoko & Kapunda, (2017) found that as the number of married people's applications for loan increases, the rate at which the number of unmarried people receiving a loan for their businesses will reduce, showing the married people are more preferred. Byrne, Tounés, Giacomin & Fattoum, (2016) found to the contrary that single entrepreneurs have higher growth intentions than married or partnered entrepreneurs.…”
Section: Response Ratementioning
confidence: 99%